Co-doped cerium oxide catalyst as well as preparation method and application thereof
By doping Co and introducing the oxygen vacancies defect structure, the problems of low catalytic efficiency and metal leakage of CeO2 catalysts in micropollutant removal are solved, and the effect of efficient micropollutant degradation and low metal leakage is achieved. .
Patent Information
- Application Number
- CN202411128850.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, the CeO2 catalyst has low visible light adsorption ability and is difficult to be excited by visible light, resulting in low catalytic efficiency when removing micropollutants in water, and the Co-based catalyst has metal leakage problems, affecting ecological security and human health.
By doping Co into CeO2, a Co-doped CeO2 catalyst is formed and an oxygen vacancies defect structure is introduced, its energy band structure is optimized to improve photocatalytic performance, and the optimal performance of the catalyst is achieved by adjusting the doping ratio of Co.
The efficient degradation of micropollutants was achieved, with a degradation rate of more than 94.27%, which significantly improved the catalytic efficiency. The leakage of cobalt ions was lower than the water pollutant emission concentration limit, reducing the risk of secondary pollution to the water environment.
Smart Images

Figure CN119140102A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of micro-pollutant removal in water environment and environmental functional materials, and specifically relates to a Co-doped CeO2 catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of the economy and the progress of human production and life, micropollutants have been continuously detected in the water environment, and their potential hazards cannot be ignored. Micropollutants have the characteristics of many types, low concentrations, difficult degradation and easy bioaccumulation, which determines that they pose a potential threat to the ecosystem and human health. Permonosulfate (PMS) Fenton-like advanced oxidation technology, as a sewage deep treatment technology, can produce highly oxidizing reactive oxygen species and is considered to be one of the most promising technologies for removing micropollutants. Although PMS is a strong oxidant, it reacts too slowly directly with most micropollutants and needs to be activated. Low electron transfer efficiency and poor electron cyclicity are the key problems that limit PMS activation and thus affect the efficient removal of micropollutants. Photocatalytic technology produces photogenerated electrons that can effectively drive electron circulation. Therefore, using light to drive PMS activation to accelerate redox reactions will enable efficient degradation of organic micropollutants.
[0003] Compared with homogeneous catalysts, the advantage of using heterogeneous catalysts to activate PMS for degradation reactions is that heterogeneous catalysts such as solid-phase catalysts can be separated from the system after the reaction by filtration or centrifugation, thereby realizing catalyst recycling, and can effectively control the metal residue in the product, reduce the risk of secondary pollution, be environmentally friendly and effectively control the cost, and be more conducive to practical application. Cerium dioxide (CeO2), as an important rare earth metal oxide, has good electronic / ionic conductivity and reversible surface oxygen ion exchange due to its valence state transition, thus having high oxygen storage / release capacity and excellent redox performance, and is widely used in various catalytic fields. However, due to the stable chemical state of CeO2, low visible light adsorption capacity, fast electron-hole recombination rate, it is difficult to be excited by visible light and difficult to activate PMS, so it needs to be regulated. Element doping strategies can adjust the band structure of CeO2 and significantly optimize its photocatalytic performance, making it more suitable for degrading organic micropollutants in water. Transition metals or transition metal oxides are often used to activate PMS. Previous studies have shown that Co can effectively activate PMS to produce reactive oxygen species. However, some Co-based catalysts or oxides have metal leakage problems, which not only affect the catalytic activity of the catalyst but also cause secondary pollution of the water environment, thus threatening ecological safety and human health. Specifically, Co is a type of heavy metal. High concentrations of cobalt ions in the water environment can pose a serious threat to human health, causing human diseases such as hypotension, paralysis and diarrhea, and can also cause genetic mutations in living cells, which limits its widespread application. Therefore, solving problems such as low catalytic efficiency, slow degradation efficiency and metal leaching remains a difficult problem. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a Co-doped CeO2 catalyst, which uses Co-doped CeO2 as an electron donor to achieve light-driven PMS activation to accelerate the redox reaction to efficiently degrade micropollutants. The catalyst is optimized by introducing an oxygen vacancy defect structure and adjusting the doping ratio of Co to exhibit excellent performance, thereby providing an effective solution for treating micropollutants in water environments.
[0005] Another object of the present invention is to provide a method for preparing a Co-doped CeO2 catalyst.
[0006] Another object of the present invention is to provide an application of a Co-doped CeO2 catalyst in photocatalytic activation of PMS to degrade pollutants.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A Co-doped CeO2 catalyst comprises CeO2 with oxygen vacancy defects and Co doped in CeO2.
[0009] In the above technical solution, the Co-doped CeO2 catalyst is a nanorod-like structure.
[0010] A method for preparing a Co-doped CeO2 catalyst comprises the following steps:
[0011] Step 1, dissolving a Ce source and a Co source in a solvent, adding a NaOH solution under stirring, and continuing stirring to obtain a suspension, wherein, in terms of the amount of substance, the ratio of Ce in the Ce source to Co in the Co source is 4:(0.02-0.06).
[0012] In the step 1, the ratio of Ce in the Ce source to Co in the Co source is 4:(0.04-0.06) in terms of the amount of the substances.
[0013] In the step 1, the Ce source is Ce(NO3)3·6H2O, the Co source is Co(NO3)3·6H2O, and the solvent is deionized water.
[0014] In the step 1, the ratio of the amount of Ce in the Ce source, the volume of the solvent and the volume of the NaOH solution is 4: (4.5-5.5): (34.5-35.5), the unit of the amount of Ce is mmol, and the unit of the volume is mL.
[0015] In step 1, the NaOH solution is a mixture of NaOH and water, and the concentration of NaOH in the NaOH solution is 5.5-6.5 mol / L.
[0016] In step 1, the stirring time is 55 to 65 minutes, and the stirring temperature is room temperature.
[0017] Step 2, heating the suspension at 98-102° C. for at least 24 hours, centrifuging to obtain a precipitate, washing the precipitate, and drying to obtain a solid material;
[0018] In step 2, the heating reaction time is preferably 24 to 24.5 hours.
[0019] In step 2, the centrifugal speed is 10000-11000 r / min, and the centrifugal time is 3-5 min.
[0020] In step 2, the washing operation includes washing with deionized water and ethanol at least 3 times each in sequence.
[0021] In step 2, the drying temperature is 55-65° C., and the drying time is at least 12 hours.
[0022] Step 3, calcining the solid material at 695-705° C. for at least 50 min under a reducing atmosphere to obtain a Co-doped CeO 2 catalyst.
[0023] In step 3, the reducing atmosphere is a mixed gas of hydrogen and argon, the volume fraction of hydrogen in the mixed gas is 5-6%, and the volume fraction of argon in the mixed gas is 94-95%.
[0024] In step 3, the calcination time is 55 to 65 minutes.
[0025] The application of the above-mentioned Co-doped CeO2 catalyst in photocatalytic activation of PMS to degrade pollutants.
[0026] In the above technical solution, the pollutant is ciprofloxacin (CIP), acetaminophen (APAP), sulfamethoxazole (SMX), methylene blue (MB), rhodamine B (RhB) or tetracycline (TC).
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The Co-doped CeO2 catalyst prepared by the present invention activates PMS under light-driven conditions to accelerate the redox reaction and thereby degrade micropollutants in the system. The Co-doped CeO2 catalyst has a good degradation effect, and the degradation rate of the typical micropollutant ciprofloxacin reaches 94.27%. In addition, the Co-doped CeO2 catalyst can also be used for the degradation and removal of various antibiotics and dye pollutants, such as acetaminophen (APAP) with a degradation rate of 96.08%, and the degradation rates of methylene blue (MB) and rhodamine B (RhB) are both 100%. It has a wide range of applications and good application prospects.
[0029] (2) The Co-doped CeO2 catalyst prepared by the present invention can achieve a degradation rate of 98.15% for ciprofloxacin within 60 minutes, greatly improving the catalytic efficiency and degradation rate.
[0030] (3) The preparation method of the present invention achieves the selection and preparation of the optimal performance Co-doped CeO2 catalyst by introducing oxygen vacancy defect structure and determining the doping ratio of Co. The designed rich oxygen vacancy defects may serve as electron trap sites, which can drive electrons to concentrate on Co atoms under light, forming a highly concentrated electron density. The doped Co participates in the redox reaction through valence state transformation, provides metal reaction sites, drives electron transfer in the system, significantly improves the PMS oxidation efficiency, and thus improves the degradation rate of pollutants, providing an effective and feasible method for the application of transition metal-doped catalysts in the treatment of micropollutants.
[0031] (4) The raw materials used in the present invention are simple (Ce(NO3)3·6H2O, Co(NO3)3·6H2O and NaOH), low in cost and easily available, which is conducive to large-scale promotion. The preparation method is simple and time-saving, and can be used for small-scale operations in the laboratory and is expected to be applied in industry.
[0032] (5) The Co-doped CeO2 catalyst prepared by the present invention is doped with cobalt metal, and the leakage of cobalt ions is much lower than the water pollutant emission concentration limits of existing and newly built enterprises and the unit product benchmark discharge limits, which effectively controls metal residues and reduces the risk of secondary pollution to the water environment. It also has good stability and good application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 X-ray diffraction (XRD) patterns of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3;
[0034] Figure 2 is the transmission electron microscope (TEM), where Figure 2 (a) is a transmission electron microscopy image of the Co-doped CeO2 catalyst prepared in Example 1. Figure 2 (b) is a transmission electron microscopy image of the CeO2 nanorod material prepared in Comparative Example 2. Figure 2 (c) is a transmission electron microscopy image of the CeO2 nanorod material prepared in Comparative Example 3. Figure 2 (d) is a transmission electron microscopy image of the Co-doped CeO2 catalyst prepared in Comparative Example 1;
[0035] Figure 3 is a high-resolution transmission electron microscopy image (HRTEM), where Figure 3 (a) is a high-resolution transmission electron microscopy image of the Co-doped CeO2 catalyst prepared in Example 1. Figure 3 (b) is a high-resolution transmission electron microscopy image of the CeO2 nanorod material prepared in Comparative Example 2;
[0036] Figure 4 This is the element distribution diagram of the Co-doped CeO2 catalyst prepared in Example 1, wherein: Figure 4 (a) is the distribution diagram of all elements (Ce, Co and O), Figure 4 (b) is the single element distribution diagram and HAADF;
[0037] Figure 5 The high-resolution X-ray photoelectron (XPS) spectra of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3 are shown in FIG. Figure 5 (a) is the Ce 3d spectrum, Figure 5 (b) is the O1s spectrum;
[0038] Figure 6 Co 2p high-resolution X-ray photoelectron (XPS) spectrum of the Co-doped CeO2 catalyst prepared in Example 1;
[0039] Figure 7 The Raman spectra of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3;
[0040] Figure 8 Fourier infrared spectra (FT-IR) of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3;
[0041] Fig. 9 is the degradation performance diagram, where Fig. 9 (a) is a graph showing the degradation performance of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod material prepared in Comparative Examples 2 to 3 for ciprofloxacin. Fig. 9 (b) is a graph showing the degradation performance of the Co-doped CeO2 catalysts prepared in Examples 1 to 3 and the CeO2 nanorod material prepared in Comparative Example 2 for ciprofloxacin;
[0042] Fig.10 The degradation performance diagram of the Co-doped CeO2 catalyst prepared in Example 1 for ciprofloxacin in different degradation systems, wherein: Fig.10 (a) is the photocatalytic PMS activation system with different PMS addition amounts. Fig.10 (b) is the photocatalytic system (CeO2 / Co / Light group), the PMS activation system (CeO2 / Co / PMS group) and the photocatalytic PMS activation system (CeO2 / Co / Light / PMS group);
[0043] Fig.11 This is a graph showing the degradation performance of the Co-doped CeO2 catalyst prepared in Example 1 for different types of organic pollutants;
[0044] Fig.12 The degradation performance diagram of Co-doped CeO2 catalyst prepared in Example 1 for ciprofloxacin under different conditions is shown in FIG. Fig.12 (a) is the catalytic degradation performance affected by the pH value of the pollutant solution. Fig.12 (b) is HCO3 in the mixed solution - The catalytic degradation performance affected by the concentration. Figure (c) shows the catalytic degradation performance affected by the HA concentration in the mixed solution.
[0045] Fig.13 The physical property characterization diagram of the Co-doped CeO2 catalyst prepared in Example 1 before and after the degradation of ciprofloxacin, wherein: Fig.13 (a) is the X-ray diffraction (XRD) pattern, Fig.13 (b) is the Raman spectrum;
[0046] Fig.14 A schematic diagram of the cobalt ion leakage during the degradation of ciprofloxacin by the Co-doped CeO2 catalyst prepared in Example 1;
[0047] Fig.15 is the UV-visible diffuse reflectance spectrum, and the inset is a schematic diagram of the band gap energy, where Fig.15 (a) is the CeO2 nanorod material prepared in Comparative Example 3, Fig.15 (b) is the Co-doped CeO2 catalyst prepared in Comparative Example 1, Fig.15 (c) is the CeO2 nanorod material prepared in Comparative Example 2, Fig.15 (d) is the Co-doped CeO2 catalyst prepared in Example 1;
[0048] Fig.16 is the valence band spectrum, where Fig.16 (a) is the valence band spectrum of CeO2 nanorod material prepared in Comparative Example 3, Fig.16 (b) is the valence band spectrum of the Co-doped CeO2 catalyst prepared in Comparative Example 1, Fig.16 (c) is the valence band spectrum of CeO2 nanorod material prepared in Comparative Example 2, Fig.16 (d) is the valence band spectrum of the Co-doped CeO2 catalyst prepared in Example 1;
[0049] Fig.17(a) transient photocurrent response test results and (b) electrochemical impedance test results of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3;
[0050] Fig.18 The photoluminescence spectra of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3 are shown, wherein: Fig.18 (a) is the steady-state photoluminescence spectrum, Fig.18 (b) is the time-resolved photoluminescence spectrum;
[0051] Fig.19 This is a graph showing the degradation performance of the Co-doped CeO2 catalyst prepared in Example 1 for ciprofloxacin after the introduction of different quenchers;
[0052] Fig. 20 The electron paramagnetic resonance spectra of the Co-doped CeO2 catalyst prepared in Example 1 and the CeO2 nanorod material prepared in Comparative Example 3 are shown in FIG. Fig. 20 (a) is 1 O2 electron paramagnetic resonance spectrum, Fig. 20 (b) is ·OH / SO4· - Electron paramagnetic resonance spectrum, Fig. 20 (c) is ·O2 - Electron paramagnetic resonance spectrum. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0054] The main raw materials and their manufacturers involved in the following examples are as follows:
[0055] Cobalt nitrate hexahydrate (Co(NO3)3·6H2O), sodium hydroxide, tert-butyl alcohol, and L-histidine were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0056] Cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and isopropanol were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0057] Ciprofloxacin was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd.;
[0058] Anhydrous ethanol was purchased from Tianjin Jiangtian Chemical Technology Co., Ltd.;
[0059] Methanol was purchased from Tianjin Concord Technology Co., Ltd.;
[0060] Naphthol was purchased from Shanghai Dibai Biotechnology Co., Ltd.
[0061] The instruments and their model information involved in the following embodiments are as follows:
[0062] Intelligent magnetic stirrer (ZNCL-GS240, Tianjin Xingke Technology Co., Ltd.);
[0063] High-pressure reactor (S50, Tianjin Solomon Biotechnology Co., Ltd.);
[0064] Tube furnace (OTF-1200X-S, Hefei Kejing Material Technology Co., Ltd.);
[0065] Muffle furnace (KSL-1100X, Hefei Kejing Material Technology Co., Ltd.);
[0066] Vacuum drying oven (DZF-6030A, Shanghai Yiheng Instrument Co., Ltd.);
[0067] The xenon lamp (CEL-HXF300, Beijing Zhongjiao Jinyuan Co., Ltd.) was installed with a 420 nm cutoff filter during the photocatalytic degradation test, i.e., light above 420 nm was retained;
[0068] UV-visible spectrophotometer (UV-6100S, Shanghai Yuanxi Instrument Co., Ltd.);
[0069] Transmission electron microscope (JEOL JEM2100 F);
[0070] X-ray diffractometer (Rigaku SmartLab SE, Japan);
[0071] X-ray photoelectron spectrometer (Thermo Scientific ESCALAB 250Xi);
[0072] Raman spectrometer (Horiba LabRAM HR Evolution confocal Raman spectrometer, Japan);
[0073] Fourier transform infrared spectrometer (Thermo Scientific Nicolet iS20, USA);
[0074] Electron paramagnetic resonance spectrometer (Bruker EMX);
[0075] UV / IR-visible spectrophotometer (Shimadzu UV-3600i Plus, Japan);
[0076] Spectrophotometer (FLS1000 spectrophotometer, Edinburgh, UK);
[0077] Three-electrode quartz cell system (HGRA1, Beijing Henggong Instrument Co., Ltd.);
[0078] Inductively coupled plasma-mass spectrometer (Agilent 7800 (MS) from the United States).
[0079] In the following examples, Ce(NO3)3·6H2O, Co(NO3)3·6H2O and NaOH were all analytically pure.
[0080] In the following examples, the NaOH solution is a mixture of NaOH and water.
[0081] Examples 1 to 3
[0082] A method for preparing a Co-doped CeO2 catalyst comprises the following steps:
[0083] Step 1, dissolving the Ce source and the Co source in a solvent, slowly adding a NaOH solution (the NaOH concentration in the NaOH solution is 6 mol / L) under stirring with a strong magnetic device, and continuing stirring at room temperature for 60 minutes to obtain a suspension, wherein the Ce source is Ce(NO3)3·6H2O, the Co source is Co(NO3)3·6H2O, the solvent is deionized water, and the ratio of Ce in the Ce source to Co in the Co source is W in terms of the amount of substance, the ratio of the amount of Ce in the Ce source, the volume of the solvent and the volume of the NaOH solution is 4:5:35, the unit of the amount of substance is mmol, and the unit of the volume is mL.
[0084] Step 2, placing the suspension in an 80 mL polytetrafluoroethylene reactor, heating the reaction at 100° C. in an oven for 24 hours, centrifuging at 11000 r / min for 3 minutes to obtain a precipitate, washing it with deionized water and ethanol three times each, and drying it in a 60° C. thermostat for 12 hours to obtain a solid material.
[0085] Step 3, placing the solid material in a tubular furnace and calcining at 700°C for 60 minutes in a reducing atmosphere (the reducing atmosphere is a mixed gas of hydrogen and argon, the volume fraction of hydrogen in the mixed gas is 5% (v / v), and the volume fraction of argon in the mixed gas is 95% (v / v)) to obtain a Co-doped CeO2 catalyst, wherein, according to the feeding theory, the doping amount of Co in the Co-doped CeO2 catalyst is x%.
[0086] The doping amounts x% of W and Co in the Co-doped CeO2 catalysts prepared in Examples 1 to 3 are shown in Table 1.
[0087] Table 1
[0088] Example W Co doping amount x% Example 1 4:0.04 1% Example 2 4:0.02 0.5% Example 3 4:0.06 1.5%
[0089] Comparative Example 1
[0090] A method for preparing a Co-doped CeO2 catalyst is basically the same as Example 1, except for step 3. Step 3 of this comparative example is "placing the solid material in a muffle furnace and calcining it at 700°C for 60 minutes in an air atmosphere to obtain a Co-doped CeO2 catalyst."
[0091] Comparative Example 2
[0092] A method for preparing CeO2 nanorod material comprises the following steps:
[0093] Step 1, dissolving the Ce source in a solvent, slowly adding a NaOH solution (the NaOH concentration in the NaOH solution is 6 mol / L) under stirring with a strong magnetic device, and continuing stirring at room temperature for 60 minutes to obtain a suspension, wherein the Ce source is Ce(NO3)3·6H2O, the solvent is deionized water, the ratio of the amount of Ce in the Ce source, the volume of the solvent and the volume of the NaOH solution is 4:5:35, the unit of the amount of the substance is mmol, and the unit of the volume is mL.
[0094] Step 2, placing the suspension in an 80 mL polytetrafluoroethylene reactor, heating the reaction at 100° C. in an oven for 24 hours, centrifuging at 11000 r / min for 3 minutes to obtain a precipitate, washing it with deionized water and ethanol three times each, and drying it in a 60° C. thermostat for 12 hours to obtain a solid material.
[0095] Step 3, placing the solid material in a tubular furnace and calcining at 700°C for 60 minutes in a reducing atmosphere (the reducing atmosphere is a mixed gas of hydrogen and argon, the volume fraction of hydrogen in the mixed gas is 5% (v / v), and the volume fraction of argon in the mixed gas is 95% (v / v)) to obtain CeO2 nanorod material.
[0096] Comparative Example 3
[0097] A method for preparing a CeO2 nanorod material is basically the same as that of comparative example 2, except for step 3. Step 3 of this comparative example is "placing the solid material in a muffle furnace and calcining it at 700°C for 60 minutes in an air atmosphere to obtain a CeO2 nanorod material."
[0098] Figure 1 The X-ray diffraction (XRD) patterns of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3 are shown in FIG. Figure 1It can be seen that they all have a typical CeO2 cubic fluorite structure (the standard card number is JCPDS NO:34-0394), and the characteristic peaks correspond to the (111), (200), (220), (311), (222), (400), (331) and (420) crystal planes of CeO2 respectively.
[0099] Figure 2 is the transmission electron microscope (TEM), where Figure 2 (a) is a transmission electron microscopy image of the Co-doped CeO2 catalyst prepared in Example 1. Figure 2 (b) is a transmission electron microscopy image of the CeO2 nanorod material prepared in Comparative Example 2. Figure 2 (c) is a transmission electron microscopy image of the CeO2 nanorod material prepared in Comparative Example 3. Figure 2 (d) is a transmission electron microscopy image of the Co-doped CeO2 catalyst prepared in Comparative Example 1. Figure 2 It can be seen that Figure 2 Comparing (b) and (c), the morphology of Co-doped CeO2 catalysts did not change significantly, and both showed well-developed nanorod-like structures.
[0100] Figure 3 is a high-resolution transmission electron microscopy image (HRTEM), where Figure 3 (a) is a high-resolution transmission electron microscopy image of the Co-doped CeO2 catalyst prepared in Example 1. Figure 3 (b) is a high-resolution transmission electron microscopy image of the CeO2 nanorod material prepared in Comparative Example 2. Figure 3 It can be seen that the crystal planes (111) and (220) belonging to CeO2 can be observed in both the Co-doped CeO2 catalyst prepared in Example 1 and the CeO2 nanorod material prepared in Comparative Example 2, and no granular matter was found on the surface of the Co-doped CeO2 catalyst prepared in Example 1, nor were the corresponding cobalt oxide lattice stripes observed, indicating that Co was doped into the CeO2 lattice.
[0101] Figure 4 This is the element distribution diagram of the Co-doped CeO2 catalyst prepared in Example 1, wherein: Figure 4 (a) is the distribution diagram of all elements (Ce, Co and O), Figure 4 (b) is a single element distribution diagram and HAADF, from Figure 4 It can be seen that the three elements (Ce, Co and O) are uniformly distributed in the Co-doped CeO2 catalyst prepared in Example 1.
[0102] Figure 5The high-resolution X-ray photoelectron (XPS) spectra of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3 are shown in FIG. Figure 5 (a) is the Ce 3d spectrum, Figure 5 (b) is the O1s spectrum. The Ce spectrum can be fitted into 8 peaks, which are respectively attributed to the 3d 5 / 2 State and 3D 3 / 2 Among them, Figure 5 The peaks “v1” and “u1” in (a) belong to Ce 3+ The remaining six peaks can correspond to Ce 4+ The characteristic peaks from Figure 5 (a) shows that compared with the Co-doped CeO2 catalyst prepared in Example 1 and Comparative Example 1, and compared with the CeO2 nanorod materials prepared in Comparative Example 2 and Comparative Example 3, CeO2 has a lower oxygen partial pressure and a higher temperature. 4+ Easy to transform into Ce 3+ , Ce 3+ The content of CeO2 increases (the peak areas of v1 and u1 increase, the peak area of u1+v1 in Example 1 accounts for 1.05, 1.10 and 1.28 times of the peak area of u1+v1 in Comparative Examples 1, 2 and 3, respectively), thereby releasing oxygen ions in the lattice to generate oxygen vacancies. Therefore, the formation of oxygen vacancies in CeO2 is usually accompanied by Ce 3+ The doping of transition metal Co can increase the Ce content in the catalyst. 3+ The ratio of oxygen vacancies is increased, that is, the concentration of oxygen vacancies is increased. v ) provides direct evidence for the increase in the oxygen vacancy concentration in the Co-doped CeO2 catalyst prepared in Example 1.
[0103] Figure 6 Co 2p high-resolution X-ray photoelectron (XPS) spectrum of the Co-doped CeO2 catalyst prepared in Example 1. Figure 6 It can be seen that the Co in the Co-doped CeO2 catalyst prepared in Example 1 exists and its oxidation state is +3.
[0104] Figure 7 The Raman spectra of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3.
[0105] Figure 8The Fourier transform infrared spectra (FT-IR) of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3 are shown in FIG. Figure 8 It can be seen that at 533cm -1 The absorption peak at 1050 cm -1 and 1605cm -1 The absorption peak at 3434 cm-1 is attributed to the H2O or CO2 molecules absorbed from the surrounding environment by the nanomaterials with a large surface-to-volume ratio. -1 The broader absorption band at is attributed to the OH stretching mode and bending associated with water molecules on the CeO2 surface, which confirms that the prepared catalyst has a CeO2 structure.
[0106] Micro-pollutant degradation experiment: Under normal pressure and temperature conditions, 20 mg of catalyst was evenly dispersed in a 100 mL beaker containing 50 mL of pollutant solution to obtain a mixed solution, 3 mL of the mixed solution was filtered with a 22 μm filter membrane, distilled water was used as a reference solution, and the absorbance of the mixed solution was measured at a wavelength of 278 nm using a spectrophotometer as C0, wherein the catalyst was one of the Co-doped CeO2 catalysts prepared in Examples 1 to 3, the Co-doped CeO2 catalysts prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3, the pollutant solution included pollutants and water, and the pollutants were one of ciprofloxacin (CIP), acetaminophen (APAP), sulfamethoxazole (SMX), methylene blue (MB), rhodamine B (RhB) and tetracycline (TC), and the initial concentration of the pollutants in the pollutant solution was 20 mg / L, and the pH was 7.
[0107] The mixed solution was stirred at a speed of 500 rpm in the dark for 20 min to establish adsorption-desorption equilibrium before the mixed solution was irradiated with a xenon lamp. After the adsorption-desorption equilibrium was reached, PMS was added to the mixed solution and stirred evenly to obtain a test solution, wherein the amount of PMS added was one of 0 mg, 10 mg, 20 mg and 30 mg, and the test solution was irradiated with a 300W xenon lamp (CEL-HXF300, equipped with a 420 nm cut-off filter) for 60 min under stirring at 500 rpm to perform catalytic degradation, and 3 mL of the test solution was taken every ten minutes during the irradiation and filtered with a 22 μm filter membrane, and distilled water was used as a reference solution, and the absorbance of the test solution was measured at a wavelength of 278 nm using a spectrophotometer as C, wherein the sampling time for taking 3 mL of the test solution was 0 min, 10 min, 20 min, 30 min, 40 min, 50 min and 60 min.
[0108] according to Determine the degradation rate at different sampling times,
[0109] Fig. 9 The Co-doped CeO2 catalyst prepared in Examples 1 to 3, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod material prepared in Comparative Examples 2 to 3 are respectively used as "catalysts" in the "degradation of micropollutants experiment" to degrade pollutants (ciprofloxacin) by PMS activation (PMS addition amount is 20 mg), wherein, Fig. 9 (a) is a graph showing the degradation performance of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod material prepared in Comparative Examples 2 to 3 for ciprofloxacin. Fig. 9 (b) is a graph showing the degradation performance of Co-doped CeO2 catalysts prepared in Examples 1 to 3 and CeO2 nanorod materials prepared in Comparative Example 2 for ciprofloxacin.
[0110] from Fig. 9 (a) shows that the degradation performance of CeO2 nanorod material prepared in comparative example 3 for ciprofloxacin is not ideal, and the degradation rate after 60 minutes of illumination is only about 20%. After doping with Co, the degradation performance of the Co-doped CeO2 catalyst prepared in comparative example 1 is significantly improved, and the degradation performance of the Co-doped CeO2 catalyst prepared in example 1 is the best after the introduction of oxygen vacancy defects. The degradation rate of the Co-doped CeO2 catalyst prepared in example 1 after 60 minutes of illumination reaches 94.27%. Fig. 9 (b) shows that compared with the CeO2 nanorod material prepared in Comparative Example 2, the degradation performance of the catalysts with different Co doping ratios is significantly improved. Within 60 minutes, the organic micropollutants can be effectively degraded with a degradation rate of more than 90%. The degradation rates of the Co-doped CeO2 catalyst prepared in Example 1 and the Co-doped CeO2 catalyst prepared in Example 3 after 60 minutes of illumination are as high as 94.27% and 98.15%, respectively. Both show excellent degradation performance without obvious gap. Therefore, in the case that both have excellent degradation performance, considering the reasons of catalyst cost saving and reducing the leakage of cobalt ions, a higher Co doping ratio is no longer considered. Therefore, the Co-doped CeO2 catalyst prepared in Example 1 is more valuable in application.
[0111] Fig.10 (a) is a graph showing the degradation performance of the Co-doped CeO2 catalyst prepared in Example 1 as a "catalyst" in the "degradation of micropollutants experiment" for degradation of pollutants (ciprofloxacin) by PMS activation (PMS addition amounts were 0 mg, 10 mg, 20 mg and 30 mg, respectively). Fig.10From (a), it can be seen that when the PMS addition amount is 20 mg and 30 mg, there is no obvious difference in the degradation effect, both of which are better than the degradation effect of PMS addition amount of 10 mg. Considering the problem of reducing the pollution caused by sulfate leaching during the degradation process, the PMS addition amount of 20 mg was selected for the experiment.
[0112] Three groups of experiments were set up: CeO2 / Co / PMS group, CeO2 / Co / Light group and CeO2 / Co / Light / PMS group. The degradation performance of the three groups of experiments is shown in Fig.10 As shown in (b), where:
[0113] CeO2 / Co / PMS group: basically the same as the "degradation of micropollutants experiment" (the catalyst is the Co-doped CeO2 catalyst prepared in Example 1, the amount of PMS added is 20 mg, and the pollutant is ciprofloxacin), the only difference is that no xenon lamp irradiation is performed. The degradation performance is as follows Fig.10 As shown in "CeO2 / Co / PMS" in (b);
[0114] CeO2 / Co / Light group: basically the same as the "degradation of micropollutants experiment" (the catalyst is the Co-doped CeO2 catalyst prepared in Example 1, and the pollutant is ciprofloxacin), the only difference is that no PMS is added (i.e., the amount of PMS added is 0 mg). The degradation performance is as follows Fig.10 As shown in "CeO2 / Co / Light" in (b);
[0115] CeO2 / Co / Light / PMS group: consistent with the "degradation of micropollutants experiment" (the catalyst is the Co-doped CeO2 catalyst prepared in Example 1, the amount of PMS added is 20 mg, and the pollutant is ciprofloxacin), the degradation performance is as follows Fig.10 As shown in “CeO2 / Co / Light / PMS” in (b).
[0116] from Fig.10 (b) shows that the degradation rate of ciprofloxacin by the coupled system of photocatalysis and PMS activation is 94.27% in 60 min, which is higher than that of single photocatalysis (26.17% in 60 min) or single PMS activation (69.91% in 60 min).
[0117] Fig.11The degradation performance diagram of the Co-doped CeO2 catalyst prepared in Example 1 as the "catalyst" in the "degradation of micropollutants experiment" for PMS activation (PMS addition amount is 20 mg) to degrade pollutants (the pollutants are acetaminophen (APAP), sulfamethoxazole (SMX), methylene blue (MB), ciprofloxacin (CIP), rhodamine B (RhB) or tetracycline (TC)), from Fig.11 It can be seen that after 60 minutes of illumination, the degradation rate of acetaminophen (APAP) by the Co-doped CeO2 catalyst prepared in Example 1 is 96.08%, the degradation rate of sulfamethoxazole (SMX) is 85.39%, the degradation rate of methylene blue (MB) and rhodamine B (RhB) is 100%, and the degradation rate of tetracycline (TC) is 98.33%. In summary, in addition to the typical micropollutant ciprofloxacin, the Co-doped CeO2 catalyst prepared in Example 1 can also be used for the catalytic removal of various types of organic pollutants, and all have relatively excellent degradation performance. Therefore, the Co-doped CeO2 catalyst of the present invention can achieve effective degradation of various organic micropollutants such as antibiotics and dyes.
[0118] Further study of the pH value of the pollutant (ciprofloxacin) solution, HCO3 in the mixed solution - The concentration of HA and the effect of HA in the mixed solution on the degradation performance. When the pH of the pollutant solution (the pollutant is ciprofloxacin) is 5, 6, 7, 8 or 9, the Co-doped CeO2 catalyst prepared in Example 1 is used as the "catalyst" in the "degradation of micropollutants experiment" to degrade pollutants by PMS activation (PMS addition amount is 20 mg). The degradation performance is as follows Fig.12 As shown in (a), the pH value of the pollutant solution is adjusted by hydrochloric acid or sodium hydroxide aqueous solution, wherein the concentration of HCl in the hydrochloric acid is 0.1 mol / L, and the concentration of sodium hydroxide (NaOH) in the sodium hydroxide aqueous solution is 0.1 mol / L.
[0119] The Co-doped CeO2 catalyst prepared in Example 1 was used as the "catalyst" in the "degradation of micropollutants experiment" to degrade the pollutant (the pollutant was ciprofloxacin) by PMS activation (the amount of PMS added was 20 mg). The pH of the pollutant solution was 7, and the mixed solution also contained HCO3 - , HCO3 - The concentration of is adjusted to 0mmol / L, 1mmol / L, 2mmol / L or 5mmol / L by adding a certain amount of NaHCO3. Fig.12 as shown in (b).
[0120] The Co-doped CeO2 catalyst prepared in Example 1 was used as the "catalyst" in the "degradation of micropollutants experiment" to activate PMS (the amount of PMS added was 20 mg) to degrade pollutants (the pollutant was ciprofloxacin). The degradation performance was as follows: Fig.12 As shown in (c), the pH of the pollutant solution is 7, the mixed solution also contains HA, and the concentration of HA is adjusted to 0 mg / L, 20 mg / L, 30 mg / L, 40 mg / L or 50 mg / L by adding a certain mass of HA (humic acid).
[0121] Fig.12 The degradation performance diagram of Co-doped CeO2 catalyst prepared in Example 1 for ciprofloxacin under different conditions is shown in FIG. Fig.12 (a) is the catalytic degradation performance affected by the pH value of the pollutant solution. Fig.12 (b) is HCO3 in the mixed solution - The concentration affects the catalytic degradation performance. Fig.12 (c) is the catalytic degradation performance affected by the HA concentration in the mixed solution. Fig.12 It can be seen that the degradation performance of the Co-doped CeO2 catalyst prepared in Example 1 for ciprofloxacin is basically not affected by the above environmental factors (pH, HA and HCO3 - ), the Co-doped CeO2 catalyst synthesized by this preparation method has good application prospects in actual wastewater treatment.
[0122] The Co-doped CeO2 catalyst prepared in Example 1 was used as the "catalyst" in the "degradation of micropollutants experiment" to degrade pollutants (the pollutant was ciprofloxacin) by activating PMS (the amount of PMS added was 20 mg) for 60 minutes. The Co-doped CeO2 catalyst prepared in Example 1 before and after degradation was characterized, as shown in FIG. Fig.13 As shown, Fig.13 The physical properties of the Co-doped CeO2 catalyst prepared in Example 1 before and after the degradation of ciprofloxacin are characterized in Figure 1, wherein (a) is an X-ray diffraction (XRD) pattern, and (b) is a Raman pattern. Fig.13 It can be seen that after the degradation reaction, the properties and structure of the Co-doped CeO2 catalyst prepared in Example 1 did not change significantly, the catalyst is stable, and its application prospect in the degradation treatment of organic micropollutants is worth looking forward to.
[0123] The Co-doped CeO2 catalyst prepared in Example 1 was used as the "catalyst" in the "degradation of micropollutants experiment" to activate PMS (the amount of PMS added was 20 mg) to degrade the pollutant (the pollutant was ciprofloxacin) for 120 min. When the degradation time was 30 min, 60 min and 120 min respectively, 5 mL of the test solution was taken to test the cobalt ion leakage. Fig.14Schematic diagram of the cobalt ion leakage during the degradation of ciprofloxacin by the Co-doped CeO2 catalyst prepared in Example 1. Fig.14 It can be seen that the leakage of cobalt ions is far lower than the water pollutant emission concentration limits of existing and newly built enterprises and the unit product benchmark discharge limit (GB 25467-2010, Co emission limit is 1000ug / L).
[0124] Fig.15 is the UV-Vis diffuse reflectance spectrum, the cut-off position in the UV-Vis diffuse reflectance spectrum is the wavelength threshold λg, and the inset is the band gap energy diagram, which is based on the Tauc Plot method (formula: (αhv) 2 =k(hv-Eg)), the intersection position in the band gap energy diagram is the band gap energy Eg, where α is the absorption coefficient and hv is the photon energy k is a constant that is independent of the photon energy. Fig.15 (a) is the CeO2 nanorod material prepared in Comparative Example 3, Fig.15 (a) shows that the wavelength threshold λg of the CeO2 nanorod material prepared in Comparative Example 3 is 428.45nm, and the band gap energy Eg is 3.00eV. Fig.15 (b) is the Co-doped CeO2 catalyst prepared in Comparative Example 1. Fig.15 (b) shows that the wavelength threshold λg of comparative example 1 is 438.44nm, and the band gap energy Eg is 2.95eV. Fig.15 (c) is the CeO2 nanorod material prepared in Comparative Example 2, Fig.15 (c) shows that the wavelength threshold λg of comparative example 2 is 435.56nm, and the band gap energy Eg is 3.00eV. Fig.15 (d) is the Co-doped CeO2 catalyst prepared in Example 1, Fig.15 (d) shows that the wavelength threshold λg of Example 1 is 439.67nm, and the band gap energy Eg is 2.97eV. The above results show that the maximum light absorption edge of the CeO2 nanorod materials prepared in Comparative Examples 2 to 3, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the Co-doped CeO2 catalyst prepared in Example 1 are all near 435nm, and have good response in the visible light range, which is conducive to the occurrence of photocatalytic reaction.
[0125] Fig.16 is the valence band spectrum, where Fig.16 (a) is the valence band spectrum of CeO2 nanorod material prepared in Comparative Example 3, and the valence band position E CB is 2.48eV, Fig.16 (b) is the valence band spectrum of the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the valence band position E CB is 2.61eV, Fig.16 (c) is the valence band spectrum of CeO2 nanorod material prepared in Comparative Example 2, and the valence band position E CB is 2.31eV, Fig.16 (d) is the valence band spectrum of the Co-doped CeO2 catalyst prepared in Example 1, and the valence band position E CB is 2.47 eV. According to formula E VB =E g +E CB The conduction band position E can be obtained VB . Focus on the conduction band position E of the Co-doped CeO2 catalyst prepared in Example 1 VB -0.5eV, its photocatalytic degradation ability can be better, therefore, combined with Fig.15 It can be seen that the CeO2 nanorod materials prepared in Comparative Examples 2 to 3, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the Co-doped CeO2 catalyst prepared in Example 1 have suitable band gap energy Eg and conduction band position Eg. VB , valence band position E CB , so that the light-driven PMS activation-accelerated redox reaction can occur smoothly in the visible light range.
[0126] Photoelectric performance test:
[0127] A method for preparing a photoanode: 0.02 g of a catalyst, 1 mL of anhydrous ethanol and 20 μL of naphthol are mixed by ultrasonication, and then dropped onto an indium tin oxide glass and dried to obtain a photoanode, wherein the catalyst is one of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1 and the CeO2 nanorod material prepared in Comparative Examples 2 to 3.
[0128] The three-electrode quartz cell system includes a reference electrode, a counter electrode and a photoanode, wherein the reference electrode is a saturated calomel electrode, the counter electrode is a platinum sheet electrode, and a Na2SO4 aqueous solution with a Na2SO4 concentration of 0.5 mol / L is used as an electrolyte.
[0129] The photoelectric performance test was carried out using an electrochemical workstation with a three-electrode quartz cell system and a 300W xenon lamp (CEL-HXF300, equipped with a 420nm cutoff filter) as the light source. The light source was turned on at 0s, turned off at 10s, turned on at 20s, turned off at 30s, turned on at 40s, turned off at 50s, turned on at 60s, and turned off at 70s. Fig.17 Transient photocurrent response test results and chemical impedance test results.
[0130] from Fig.17It can be seen that the Co-doped CeO2 catalyst prepared in Example 1 has a higher photocurrent response and a smaller impedance radius, indicating that it has a higher electron-hole separation efficiency and a lower interface resistance, which is beneficial to the transfer of photoelectrons.
[0131] Fig.18 The photoluminescence spectra of the Co-doped CeO2 catalyst prepared in Example 1, the Co-doped CeO2 catalyst prepared in Comparative Example 1, and the CeO2 nanorod materials prepared in Comparative Examples 2 to 3 are shown, wherein: Fig.18 (a) is the steady-state photoluminescence spectrum. Fig.18 It can be seen from (a) that the peak fluorescence emission intensity of the Co-doped CeO2 catalyst prepared in Example 1 is the lowest, indicating that the doping of Co and the introduction of oxygen vacancies can improve the separation efficiency of photogenerated carriers, thereby improving the charge transfer efficiency and inhibiting the recombination of electrons and holes. Fig.18 (b) is the time-resolved photoluminescence spectrum, from Fig.18 (b) shows that the fluorescence lifetime of the CeO2 nanorod material prepared in Comparative Example 3 is 17.30ns, the fluorescence lifetime of the Co-doped CeO2 catalyst prepared in Comparative Example 1 is 23.37ns, the fluorescence lifetime of the CeO2 nanorod material prepared in Comparative Example 2 is 21.49ns, and the fluorescence lifetime of the Co-doped CeO2 catalyst prepared in Example 1 is 35.70ns. The above results show that the Co-doped CeO2 catalyst prepared in Example 1 has the longest fluorescence lifetime, indicating that it has the best inhibitory effect on the recombination of electron-hole pairs, which is conducive to the occurrence of catalytic degradation reactions.
[0132] No quencher experiment: The Co-doped CeO2 catalyst prepared in Example 1 was used as the "catalyst" in the "degradation of micropollutants experiment" to degrade the pollutant (ciprofloxacin) by PMS activation (PMS addition amount was 20 mg) as the "no quencher" in the figure.
[0133] Six parallel experiments were performed with reference to the above-mentioned quencher-free experiment: in the parallel experiments, a quencher was added to the mixed solution at the same time as PMS was added, and the quencher was one of tert-butyl alcohol (TBA), methanol (MeOH), silver nitrate (AgNO3), triethanolamine (TEOA), superoxide dismutase (SOD) and L-histidine (L-histidine), wherein the final concentration of methanol in the mixed solution was 0.5 mol / L, the final concentration of silver nitrate in the mixed solution was 100 mg / L, the final concentration of triethanolamine in the mixed solution was 1 mmol / L, the final concentration of superoxide dismutase (SOD) in the mixed solution was 200 units / mL, and the final concentration of L-histidine in the mixed solution was 10 mmol / L.
[0134] The quencher tert-butyl alcohol (TBA) was added to quench the hydroxyl radical ·OH in the system, and the quencher methanol (MeOH) was added to quench the sulfate radical SO4· - and hydroxyl radicals ·OH, adding quencher silver nitrate (AgNO3) to quench the free electrons in the system - , add quencher triethanolamine (TEOA) to quench the holes in the system h + , add quencher superoxide dismutase (SOD) to quench the superoxide free radicals in the system. - And add the quencher L-histidine to quench the singlet oxygen in the system 1 O2 is used to detect active substances involved in the degradation reaction. Fig.19 The degradation performance diagram of ciprofloxacin by the Co-doped CeO2 catalyst prepared in Example 1 after the introduction of different quenchers is shown in FIG. Fig.19 It can be seen that compared with the absence of quencher, the degradation performance after adding tert-butyl alcohol, superoxide dismutase and silver nitrate respectively did not change much, while the degradation performance after adding methanol, L-histidine and triethanolamine quencher respectively decreased significantly, which further indicated that there was SO4· - Participate in degradation, 1 O2 and H + It is the main active substance in the degradation process.
[0135] Method for obtaining electron paramagnetic resonance spectrum (the catalyst below is one of the Co-doped CeO2 catalyst prepared in Example 1 and the CeO2 nanorod material prepared in Comparative Example 3):
[0136] 1. Detection 1 O2: Add 3 mg of catalyst and 3 mL of ultrapure water into a 5 mL centrifuge tube, use a 300 W xenon lamp (CEL-HXF300, equipped with a 420 nm cutoff filter) as the light source to illuminate the reaction for 5 min. After 5 min, add 30 μL of 4-amino-2,2,6,6-tetramethylpiperidine (TEMP) into the centrifuge tube. 1 O2 is captured and the results of the electron paramagnetic resonance spectrum are as follows Fig. 20 As shown in (a).
[0137] 2. Detection of OH and SO4 - : 3 mg of catalyst and 3 mL of ultrapure water were added to a 5 mL centrifuge tube, and a 300 W xenon lamp (CEL-HXF300, equipped with a 420 nm cutoff filter) was used as the light source for the reaction for 5 min. After 5 min, 30 μL of 5,5-dimethyl-1-pyrroline N-oxide (DMPO) was added to the centrifuge tube to react with ·OH and SO4· - Capture and test the results of electron paramagnetic resonance spectroscopy. Fig. 20 as shown in (b).
[0138] 3. Detection of O2 - : 3 mg of catalyst and 3 mL of methanol were added to a 5 mL centrifuge tube, and a 300 W xenon lamp (CEL-HXF300, equipped with a 420 nm cutoff filter) was used as the light source for the reaction for 5 min. After 5 min, 30 μL of 5,5-dimethyl-1-pyrroline N-oxide (DMPO) was added to the centrifuge tube to react with ·O2 - Capture and test the results of electron paramagnetic resonance spectroscopy. Fig. 20 as shown in (c).
[0139] from Fig. 20 As shown in (a), a clear 1 The 1:1:1 triplet characteristic ESR signal of CeO2 was obtained, but only a weak signal was found in the electron paramagnetic resonance spectrum of the CeO2 nanorod material prepared in Comparative Example 3, indicating that the Co-doped CeO2 catalyst prepared in Example 1 produced a large amount of 1 O2 reactive oxygen species. Fig. 20 (b) shows that SO4· - The characteristic ESR signal of the CeO2 nanorod material prepared in Comparative Example 3 was not observed in the electron paramagnetic resonance spectrum, indicating that SO4· - In addition, Fig. 20 In (c), no obvious O2 was detected in the electron paramagnetic resonance spectra of the Co-doped CeO2 catalyst prepared in Example 1 and the CeO2 nanorod material prepared in Comparative Example 3. - In summary, it can be seen that the active species involved in the catalytic degradation process include SO4· - and 1 O2.
[0140] The present invention prepares a Co-doped CeO2 catalyst with an optimal Co doping ratio and an oxygen vacancy defect structure by doping transition metal Co into CeO2, further regulating the doping ratio of Co and introducing an oxygen vacancy defect structure. The Co-doped CeO2 catalyst can effectively inhibit the recombination of charge carriers, improve the utilization rate of holes and the energy transfer efficiency, thereby promoting the efficient generation of active species, greatly improving the PMS activation efficiency and catalytic performance, and achieving efficient degradation of micropollutants.
[0141] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A Co-doped CeO2 catalyst, characterized in that: include: CeO2 with oxygen vacancy defects and Co doped in CeO2.
2. A method for preparing a Co-doped CeO2 catalyst, characterized in that: The following steps are involved: Step 1, dissolving a Ce source and a Co source in a solvent, adding a NaOH solution under stirring, and continuing to stir to obtain a suspension, wherein, based on the amount of substance, the ratio of Ce in the Ce source to Co in the Co source is 4: (0.02-0.06); Step 2: heating the suspension at 98-102° C. for at least 24 hours, centrifuging to obtain a precipitate, washing the precipitate, and drying to obtain a solid material; Step 3: calcining the solid material at 695-705° C. for at least 50 min under a reducing atmosphere to obtain a Co-doped CeO 2 catalyst.
3. The preparation method according to claim 2, characterized in that In step 1, the ratio of the amount of Ce in the Ce source, the volume of the solvent and the volume of the NaOH solution is 4: (4.5-5.5): (34.5-35.5), the unit of the amount of Ce is mmol, and the unit of the volume is mL.
4. The preparation method according to claim 2, characterized in that In step 1, the NaOH solution is a mixture of NaOH and water, and the concentration of NaOH in the NaOH solution is 5.5 to 6.5 mol / L.
5. The preparation method according to claim 2, characterized in that In step 2, the heating reaction time is preferably 24 to 24.5 hours.
6. The preparation method according to claim 2, characterized in that In step 2, the washing operation includes washing with deionized water and ethanol at least three times each.
7. The preparation method according to claim 2, characterized in that In step 3, the reducing atmosphere is a mixed gas of hydrogen and argon, the volume fraction of hydrogen in the mixed gas is 5-6%, and the volume fraction of argon in the mixed gas is 94-95%.
8. The preparation method according to claim 2, characterized in that In step 3, the calcination time is 55 to 65 minutes.
9. The preparation method according to claim 2, characterized in that In step 2, the drying temperature is 55-65° C., and the drying time is at least 12 hours.
10. Use of the Co-doped CeO2 catalyst as claimed in claim 1 in photocatalytic activation of PMS to degrade pollutants.
